Composite Materials Based on Henequen Fiber as a Thermal Barrier in the Automotive Sector. (14th July 2019) - Olivares-Ramírez, J. M.; Dector, A.; Duarte-Moller, A.; Ortega Díaz, D.; Dector, Diana; Cano-López, J. A.; Rangel-Martínez, R.; Pérez-Bueno, J. J.; Castañeda-Miranda, A.; Tovar-Pacheco, Felipe Samuel
Abstract : Currently, the automotive industry has made great advances in the incorporation of materials such as carbon fiber in high-performance cars. One of the main problems of these vehicles is warming, which is generated inside due to the heat transfer produced by solar radiation falling on the car, mainly on the roof. This research proposes the preparation of a composite material containing henequen natural fiber as a thermal barrier to be used as the roof of the car. In this research, 35 different laminates of 5 layers were prepared, combining carbon fiber, henequen natural fiber, fiberglass, and additives such as resin + Al2 O3 or resin + Al. Reference samples were taken from stainless steel and one reference sample was extracted from the roof of the car. Considering the solar radiation and the heat transfer mechanisms, the temperature of the surface exposed to solar radiation was determined. The thermal conductivity of the 37 samples was determined, and the experimental results showed that the thermal conductivity of the steel with which the roof of the car is manufactured was 13.43 W·m −1 ·K −1 and that of the proposed laminate was 5.22 W·m −1 ·K −1, achieving a decrease in the thermal conductivity by 61.13%. Using the temperature and thermal conductivity data, the simulation (ANSYS) of the thermal system was performed. The results showed that the temperature inside the car with the carbon steel, which is currently used to manufacture high-performance cars, would be 62.34°C, whereas that inside the car with the proposed laminate would be 44.96°C, achieving a thermal barrier that allows a temperature difference of 17.38°C.